Peningkatan Pemahaman Mufradāt Afrād al-Usrah melalui Mind Map dan Word Wall - Azka Luthfiyatul Kamilah; Naira Atha Khalilah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic language learning has an important role as an international language. One of the main challenges faced by beginners is the lack of use of innovative learning media, so that the learning process becomes monotonous and less interesting, especially in understanding mufrodat afrād al-usrah. This research uses a qualitative method with a descriptive approach. Mind map and word wall learning media were applied to help students understand mufrodat afrād al-usrah. Data were collected through observations and interviews to describe the effectiveness of the media. The use of mind map and word wall media was proven to improve students' understanding of mufrodat afrād al-usrah. Students showed improvement in remembering and applying the learnt vocabulary. Data analysis showed that mind maps help students organise information visually, making it easier to understand and remember new words. Word wall serves as a constant reminder that motivates students to actively interact with the vocabulary. The combination of these two media reduces boredom and increases student engagement in the learning process. Data showed that the average pretest score of students was 60, which increased significantly to an average posttest score of 80 after the application of these media. This indicates that the application of innovative learning media can replace conventional methods that are less effective in improving mufrodat comprehension. The application of innovative learning media such as mind map and word wall can overcome boredom and monotony in Arabic language learning, thus increasing students' motivation to learn.